2002
DOI: 10.1037/0893-164x.16.4.338
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among gender, depression and needle sharing in a sample of injection drug users.

Abstract: The authors explored the relationships among gender, needle sharing, and depression in a sample of 392 male and 121 female street drug users. Using the Risk Behavior Assessment (National Institute on Drug Abuse, 1991) and the Beck Depression Inventory-2 (A. T. Beck, R. A. Steer, & G. K. Brown, 1996), the authors found that women reported higher levels of depression than men and that sharers endorsed higher levels of depression than nonsharers. Further, the authors found that female sharers reported the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 23 publications
4
18
0
1
Order By: Relevance
“…Our results regarding needle sharing are consistent with previous literature suggesting a correlation between psychiatric symptoms severity and the propensity of PWID to share needles [25][26][27]29,30,34,44]. More specifically, two studies have previously demonstrated an association between severe psychological distress and injection material sharing (including needles) among an undifferentiated sample of PWID [35,36].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our results regarding needle sharing are consistent with previous literature suggesting a correlation between psychiatric symptoms severity and the propensity of PWID to share needles [25][26][27]29,30,34,44]. More specifically, two studies have previously demonstrated an association between severe psychological distress and injection material sharing (including needles) among an undifferentiated sample of PWID [35,36].…”
Section: Discussionsupporting
confidence: 82%
“…Cocaine use and mental health disorders have both been identified as risk factors for material sharing [9][10][11][12][13]22,[23][24][25][26][27][28][29][30][31][32][33][34]. Over a third of our participants reported severe psychological distress, a higher proportion compared with the 20% prevalence rate found in the Canadian population [43].…”
Section: Discussionmentioning
confidence: 72%
“…Among IDUs under 30, females were more likely to share syringes than males (Evans et al, 2003;Montgomery et al 2002). High levels of depression symptoms were also associated with increased risk of syringe sharing (Johnson, Yep, Brems, Theno, & Fisher, 2002;Mandell, Kim, Latkin, & Shuh, 1999;Perdue, Hagan, Thiede, & Valleroy, 2003). A study of SEP participants in New York City found that respondents who injected cocaine daily were more likely to share syringes (Paone et al 1997).…”
Section: Long-term Effects Of Syringe Exchange On Risk Behavior and Hmentioning
confidence: 94%
“…[20][21][22] Entre as mulheres com AOS, 19% tiveram depressĂŁo em algum momento na vida, enquanto que na população geral de mulheres essa prevalĂȘncia Ă© de 7%. Nos homens com AOS, 78% apresentaram primeiro AOS e depois depressĂŁo; entre as mulheres com AOS, 66% apresentaram primeiro a depressĂŁo.…”
unclassified